Model Pengembangan Green Business melalui Corporate Social Responsibility pada Perusahaan Go Public di Bursa Efek Indonesia - Sri Handoko (STIE Widya Manggala, 2012)
The issue of environmental degradation, air pollution, floods, difficulties in water supply, high prices of basic necessities, and use of hazardous substances that harm consumers have inspired people to the importance of the concept of the Green Economy that synergizes economic value, social, and environmental. This research is very important to do because Green Business which is part of the Green Economy has been applied by some companies that went public on the Indonesia Stock Exchange. This research aimed to look into and analyze the Development Model Green Business through Corporate Social Responsibility Program, which is expected to improve financial performance and market performance.The population of this research was companies that to go public on the Indonesia Stock Exchange. The sample of this research were 30 companies that go public and become a member of PROPER (Assessment of Corporate Environmental Concern, which were observed 2007.2008, and 2009. Statistic Analysis used was multiple regression.The results of this research generally indicated that the Green Business had a negative effect on financial performance, as well as having a positive impact on market performance, but it was not significantly. In addition Corporate Social Responsibility was not able to act as a moderating variable in raising financial performance and market performance.